1987
DOI: 10.1073/pnas.84.23.8530
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pHV2 from Halobacterium volcanii and its use in demonstrating transformation of an archaebacterium.

Abstract: We determined the complete nucleotide sequence of the 6354-base-pair plasmid pHV2 of the archaebacterium Halobacterium vokcanii. This plasmid is present in approximately six copies per chromosome. We have generated a strain, H. volcanii WFD11, cured of pHV2 by treatment of liquid cultures with ethidium bromide. We describe PEGmediated transformation of H. volcanii WFD11 with intact pHV2 and with a form of pHV2 marked by a 93-base-pair deletion generated in vitro.Since the recognition that the archaebacteria ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
87
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(89 citation statements)
references
References 29 publications
2
87
0
Order By: Relevance
“…Since their discovery in the 1970s, many surprising features have been reported, such as their unique membrane lipids and the presence of genes containing introns, and they remain of great biological interest (for a review, see reference 31). Within the archaebacterial kingdom, the halobacteria, and particularly members of the genus Haloferax, are the most convenient group for genetic study (6,7), but until recently the analysis of gene structure and function had been frustrated by the unavailability of genetic systems, with much of the work being limited to sequence comparisons with eubacterial and eucaryotic homologs.…”
mentioning
confidence: 99%
“…Since their discovery in the 1970s, many surprising features have been reported, such as their unique membrane lipids and the presence of genes containing introns, and they remain of great biological interest (for a review, see reference 31). Within the archaebacterial kingdom, the halobacteria, and particularly members of the genus Haloferax, are the most convenient group for genetic study (6,7), but until recently the analysis of gene structure and function had been frustrated by the unavailability of genetic systems, with much of the work being limited to sequence comparisons with eubacterial and eucaryotic homologs.…”
mentioning
confidence: 99%
“…gari BCC 24369, followed by NaCl, and MgSO 4 ·7H 2 O, respectively (p < 0.01). Casamino acid, a partially hydrolyzed casein containing nitrogen, vitamin, carbon and amino acids, is commonly used in culture media for haloarchaeal growth (Charlebios et al, 1987). Patel et al (2005) also reported that casamino acid was the most important factor affecting protease production by haloalkaliphilic Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Gene transfer systems reported for archaebacteria include mating (12,14) and transformation with genomic (1,4,16), plasmid (2,6), or bacteriophage DNA (3). Recently, gene transfer by a transductionlike process in Methanococcus voltae was reported (G. Bertani, Abstr.…”
mentioning
confidence: 99%